2013
DOI: 10.1371/journal.pone.0055104
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Targeted Delivery of a c-Myc Inhibitory Polypeptide Inhibits Tumor Progression and Extends Survival in a Rat Glioma Model

Abstract: Treatment of glioblastoma is complicated by the tumors’ high resistance to chemotherapy, poor penetration of drugs across the blood brain barrier, and damaging effects of chemotherapy and radiation to normal neural tissue. To overcome these limitations, a thermally responsive polypeptide was developed for targeted delivery of therapeutic peptides to brain tumors using focused hyperthermia. The peptide carrier is based on elastin-like polypeptide (ELP), which is a thermally responsive biopolymer that forms aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 40 publications
6
102
1
Order By: Relevance
“…Enhanced levels of MYC are thought to contribute to genesis of many human tumors, including glioma. [11][12][13] These results suggested that USP28 plays a role in the oncogenesis of some malignancies. However, whether USP28 expression contributes to glioma development and progression is unknown.…”
Section: Introductionmentioning
confidence: 78%
“…Enhanced levels of MYC are thought to contribute to genesis of many human tumors, including glioma. [11][12][13] These results suggested that USP28 plays a role in the oncogenesis of some malignancies. However, whether USP28 expression contributes to glioma development and progression is unknown.…”
Section: Introductionmentioning
confidence: 78%
“…Due to its key role in tumorigenesis, much recent research has been directed to finding ways to target c-MYC function (24)(25)(26)(27)(28)(29). Dominant-negative approaches targeting c-MYC function impair intestinal tumor formation, and c-Myc heterozygous mice show reduced tumor development in the Apc min/+ model (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed an 80% reduction in tumour volume after hyperthermia-induced aggregation, therefore this approach was suggested to be an alternative for drug delivery to brain tumours. 49 However, experiments regarding the cellular uptake efficiency and retention of ELRs in solid tumours after hyperthermia were only performed recently. These studies showed that larger ELRs are better when these properties are taken into account.…”
Section: Fusion Recombinamersmentioning
confidence: 99%